SISTEM PENDETEKSI KERETAKAN PADA MATERIAL BATU BATA MENGGUNAKAN TEKNOLOGI COMPUTER VISION - Arifin, Samsul; Febriyanto, Bagas Aji (LPPM Universitas Bina Bangsa, 2024)
The crack detection system on brick material is an important application in the maintenance of building infrastructure. Cracks in bricks can lead to a decline in the quality and safety of building structures. This study proposes the use of computer vision technology to automatically detect cracks in bricks. The methods employed include image capture of bricks using a camera, image processing to enhance image quality, and the application of machine learning algorithms to classify the condition of the bricks. The results of this research demonstrate that the proposed system can detect cracks with high accuracy, providing an efficient solution for monitoring the condition of building materials.